Does Financial Slack Moderate Effect of Environmental, Social, and Governance (ESG) on Firm Performance? - Pujangga Abdillah; Szabyna Regytha Aura Gunawan (Economics and Digital Business Review, 2023)
The purpose of this study is to investigate the impact of ESG (Environment, Social, and Governance) on firm performance as well as the function of financial slack as a moderating variable that may enhance the impact of ESG on firm performance. Property sectors registered based on IC (Industrial Classification) in the Indonesia Stock Exchange between 2019 and 2021 make up the population of this study. Samples were taken using the judgment sampling technique with a total sample of 214 observations. The data analysis approach employed is moderated regression analysis (MRA) and data testing was performed using STATA. The findings demonstrated that ESG influences firm performance as evaluated by Return on Asset (ROA). In other words, firm performance can increase with better ESG standards. The findings of this study also demonstrate that financial slack, when used as a moderating variable, can boost the impact of ESG on firm performance.